2003
DOI: 10.1074/jbc.m301010200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ERK1/2 Signaling Pathway Promotes Phosphorylation and Proteasome-dependent Degradation of the BH3-only Protein, Bim

Abstract: Both the ERK and phosphatidylinositol 3-kinase (PI3K) signaling pathways can protect cells from apoptosis following withdrawal of survival factors. We have previously shown that the ERK1/2 pathway acts independently of PI3K to block expression of the BH3-only protein, Bim EL , and prevent serum withdrawal-induced cell death, although the precise mechanism by which ERK reduced Bim EL levels was unclear. By comparing Bim mRNA and Bim protein, expression we now show that the rapid expression of Bim EL following s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
518
6
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(574 citation statements)
references
References 29 publications
46
518
6
4
Order By: Relevance
“…As BimEL degradation occurred concomitantly with phosphorylation, we examined two phosphorylation sites on BimEL previously shown to regulate proteolysis. Erk 1 and 2 were shown to phosphorylate BimEL on S69 10,12,18 and promote degradation and phosphorylation on S93/94/98 has been shown to induce degradation through the Skp1-Cullin1-F-Box (SCF) complex. 20 In order to assess the importance of these sites for BimEL degradation in mitosis, phosphospecific antibodies were used to monitor these modifications during mitosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As BimEL degradation occurred concomitantly with phosphorylation, we examined two phosphorylation sites on BimEL previously shown to regulate proteolysis. Erk 1 and 2 were shown to phosphorylate BimEL on S69 10,12,18 and promote degradation and phosphorylation on S93/94/98 has been shown to induce degradation through the Skp1-Cullin1-F-Box (SCF) complex. 20 In order to assess the importance of these sites for BimEL degradation in mitosis, phosphospecific antibodies were used to monitor these modifications during mitosis.…”
Section: Resultsmentioning
confidence: 99%
“…4,7,8 Post-transcriptional mechanisms that have been shown to control Bim expression levels include both mRNA stability 9 and protein stability. [10][11][12] Signaling downstream of receptor tyrosine kinases (RTKs) including epidermal growth factor receptor induce the proteasomal degradation of Bim. [13][14][15][16] There are three splice variants of Bim: BimEL, BimL and BimS.…”
mentioning
confidence: 99%
“…21 Subsequently, it was shown that activation of the ERK1/2 pathway was necessary and sufficient to accelerate the turnover of Bim EL and ERK1/2-dependent Bim EL degradation was shown to proceed via the proteasome. 34 Proteasome-dependent turnover has subsequently been confirmed in other cell types. 20,30,35,36 Phosphorylation at Ser69 seems to be an important signal for turnover of Bim EL since Ser69Ala or Ser69Gly mutants are defective for turnover, accumulate to higher levels in cells and so exhibit enhanced toxicity.…”
Section: Erk1/2-dependent Phosphorylation Antagonizes Bim Elmentioning
confidence: 94%
“…Phosphorylation of BIM by ERK was reported to be critical for the antiapoptotic activity of this kinase. [56][57][58][59][60] However, a recent study has shown that ERK-mediated direct phosphorylation of BIM does not have a major role in the control of the proapoptotic activity of this BH3-only protein within the whole animal. 61 Both BIM and BMF were shown to be sequestered by binding to elements of the cytoskeleton, thereby restraining their pro-apoptotic activity.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%